Evaluation of sound-working memory therapy intervention in Autism Spectrum Disorder (ASD) children using Auditory Brainstem Response (ABR) sensory gating - Shahrudin, Fatin Amira; Dzulkarnain, Ahmad Aidil Arafat; Jamal, Fatin Nabilah; Rahmat, Sarah; Musa, Ramli; Ahmad Basri, Nadzirah; Jusoh, Masnira; Sidek, Shahrul Na'im; Md. Yusof, Hazlina; Khalid, Madihah (2021)
Background: Sound therapy is an intervention to provide extensive treatment for Autism Spectrum Disorder (ASD) children. However, there is a lack of scientific evidence on the validity of this method that has been performed in the previous studies including (i) the use of parental-report questionnaires for pre and post-intervention and (ii) an absence of objective test such as auditory-evoked potential (AEP) to evaluate the effectiveness of sound-therapy to regulate emotion in ASD children. This study aims to investigate the effectiveness of sound therapy in regulating the emotion of ASD children using Auditory Brainstem Response (ABR) Sensory Gating through Stroop Task and parental-reported questionnaires (Emotion Regulation Checklist (ERC) and Malay Sensory Gating Survey (SGS)).